Therapeutic Potential of Proanthocyanidins in Dentistry: A Focus on Periodontal Disease and on Dental Implants in Osteoporotic Patients - Yoshimi Niwano; Shunichi Shishido; Midori Shirato; Hidetsugu Kohzaki; Keisuke Nakamura (Antioxidants)
Proanthocyanidins (PACs), also called condensed tannins, are oligomers or polymers composed of flavan-3-ols. This review aimed to explore the potential role of PACs in ameliorating oral health problems, with a particular focus on their effects within the intestine—especially the colon, where most orally ingested PACs are believed to accumulate. Previous studies suggest that PACs can be beneficial in periodontal disease as well as in the osseointegration of dental implants in patients with osteoporosis. Periodontal disease is worsened by lipopolysaccharides (LPS) that enter the bloodstream due to disrupted tight junctions of intestinal epithelial cells, along with inflammatory cytokines released by activated macrophages. A similar mechanism is thought to affect osseointegration: LPS-induced inflammatory cytokines originating in the intestine can enter the bloodstream, contributing to bone loss and impaired integration of dental implants. PACs absorbed by intestinal epithelial cells can function as prooxidants, triggering the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway, which strengthens the gut barrier. This enhanced barrier reduces the levels of LPS and inflammatory cytokines in the blood, leading to the alleviation of periodontal inflammation and increased alveolar bone density, thereby promoting better osseointegration of dental implants.